The Use of YouTube Social Media in the Covid19 Pandemic to Improve Understanding of Mathematical Concepts - Almatius Setya Marsudi; Maria Pudji Lestari; Nuzulul Hidayati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to find out any improvement in mathematics learning achievements of students after using YouTube as learning media in the Covid19 Pandemic, especially improvement in mathematics learning achievements about 2-variable linear equation system of students of Class X in Semester 1 SMK Bonaventura (a vocational high School in Indonesia), 2020-2021 academic year, after using YouTube as their learning media. This research was meant to explore if there is any improvement in mathematics learning achievements of students after using YouTube as learning media, especially improvement in mathematics learning achievements about 2-variable linear equation system of students of Class X in Semester 1 SMK Bonaventura, 2020-2021 academic year after using YouTube as their learning media. The researcher utilized a quasi-experiment with a 2x2 factorial concept. A closed group of SMK Bonaventura students was used as the research sampling. The research instrument is a comprehension ability test on mathematical theories. Anakova was used to analyze collected data. The researcher found out that there are different levels of students’ cognitive ability which study via YouTube created on Corel Videostudio X10 with ethnomathematical application and which studying conventionally, after controlling students’ initial abilities. Conclusion of this research is that students studying using YouTube with ethnomathematical application by way of Corel Video Studio X10 has positively affected their conceptual cognitive ability and are better than performance of students who study conventionally after controlling students’ initial abilities.